Prevalecencia de anquiloglosia y su relación con problemas de fonación en los estudiantes de género masculino y femenino de la Universidad Nacional de Loja de la modalidad de estudios presencial en el periodo mayo-julio del 2014 - Santorun Neira, Lizeth Katherine (2014)
Tongue tie is a disorder characterized by an abnormally short lingual frenulum, causing limits the normal movements of the tongue, with a prevalence ranging from 4.2% to 10.7 % , reason if it is not treated early, difficult articulation of words , causing problems of phonation. A descriptive cross-sectional study such program, which aims to determine the prevalence of ankyloglossia and its relation to problems of phonation of the students of the University National of Loja mode Witnessed Study Period May-July 2014, examined 894 students, gathering information through the Dental Clinic History, the same that was used to build a database. The results were: 5% if they had tongue tie and the remaining 95 % had no such pathology, 54.35 % were male and 45.65 % are female gender, only 30.34 % have phonetic problems directly related with tongue tie, while 69.56 % have no phonetic problems. By indicating that the study population has a low prevalence of ankyloglossia related to phonetic problems. Keywords: tongue tie, phonation problems.